2014
DOI: 10.1002/ccd.25384
|View full text |Cite
|
Sign up to set email alerts
|

Effective endovascular treatment of calcified femoropopliteal disease with directional atherectomy and distal embolic protection: Final results of the DEFINITIVE Ca++ trial

Abstract: ObjectivesThe purpose of the DEFINITIVE Ca++ study was to evaluate the safety and effectiveness of directional atherectomy and distal embolic protection, used together to treat moderate to severely calcified femoropopliteal lesions.BackgroundDespite advances in endovascular treatment modalities, treatment of calcified lesions remains a challenge.MethodsA total of 133 subjects with 168 moderate to severely calcified lesions were enrolled. Lesions were treated with directional atherectomy devices, coupled with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 26 publications
1
62
0
2
Order By: Relevance
“…What is “moderate” calcification according to one may be considered “severe” (or vice versa) by another operator or analyst. Thus far, angiography‐based algorithms have been proposed to evaluate calcification severity in the peripheral arteries (typically superficial femoral artery [SFA]) but not in the carotid territory where the lesion characteristics show several peculiarities and where management tools have been limited in relation to the peripheral arteries such as SFA. Therefore, development of a simple (and applicable in routine practice) yet informative angiographic scoring system to grade carotid calcification has been critically important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is “moderate” calcification according to one may be considered “severe” (or vice versa) by another operator or analyst. Thus far, angiography‐based algorithms have been proposed to evaluate calcification severity in the peripheral arteries (typically superficial femoral artery [SFA]) but not in the carotid territory where the lesion characteristics show several peculiarities and where management tools have been limited in relation to the peripheral arteries such as SFA. Therefore, development of a simple (and applicable in routine practice) yet informative angiographic scoring system to grade carotid calcification has been critically important.…”
Section: Discussionmentioning
confidence: 99%
“…This has been due to an increased likelihood of dissection with vessel perforation or rupture, and inadequate angiographic results (stent fractures, stent underexpansion and/or malapposition and a greater residual stenosis) leading to suboptimal acute (including increased cerebral embolism) as well as long‐term clinical outcomes and an increased risk of in‐stent restenosis . In the coronary and peripheral (mostly superficial femoral artery) territory, several percutaneous techniques and devices have been recently developed to address challenges associated with high‐grade target lesion calcification, including scoring balloons, atherectomy devices and, more recently, intravascular lithotripsy . These techniques, however, are not applicable to the carotid lesions, and HCCS has been typically subjected to surgical management (carotid endarterectomy [CEA]) …”
Section: Introductionmentioning
confidence: 99%
“…Patients with CLI who cannot undergo bypass surgery, however, have no option other than EVT; therefore, EVT technology should progress. Recently, new devices, such as drug‐eluting stents , drug‐coated balloons , directional atherectomy , and laser atherectomy , which are not yet widely available in Japan, have resulted in a decrease in repeat EVT rates. These devices may increase wound healing rates after EVT in high‐risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…The DEFINITIVE Ca++ study involved 133 patients with 168 moderate to severely calcified femoropopliteal lesions treated with Endovascular therapy for CLI Review informahealthcare.com directional atherectomy using the Silverhawk or Turbohawk (Covidien, Plymouth, MN) and distal embolic protection. The study reported 93% freedom from major adverse events, which included clinically significant embolization [87]. Definitive clinical benefit of atherectomy over PTA is not clear.…”
Section: Atherectomymentioning
confidence: 90%